The impact of nutritional support therapy combined with conventional treatment models on short-term symptom improvement and complications in stroke patients: a systematic review and meta-analysis - Zhang, Meng; Li, Meng; Ding, Ying; Zhang, Yi; Zhang, Li; Peng, Xiapei (Frontiers in Nutrition, 2025)
ObjectiveTo methodically assess the effectiveness of nutritional support therapy combined with conventional treatment on short-term symptom improvement, nutritional and immune recovery, and complication rates in stroke patients.MethodsA thorough literature search was carried out utilizing PubMed, EMBASE, ScienceDirect, the Cochrane Library, and major Chinese databases (CNKI, VIP, Wanfang, and CBM) from inception to the present. Randomized controlled trials (RCTs) evaluating the impact of nutritional support in stroke patients were included. Two reviewers independently extracted the data, and the Cochrane Handbook 5.3 was used to determine the risk of bias. RevMan 5.3 was used to conduct the meta-analysis.ResultsFollowing PRISMA guidelines, 1,693 records were retrieved and screened, resulting in the inclusion of 8 randomized controlled trials with a total of 727 individuals. Meta-analysis revealed that nutritional support significantly improved Glasgow Coma Scale (GCS) scores, serum markers of nutritional status (Hb, TLC), and immune parameters (IgA, IgG, IgM). Pro-inflammatory cytokines (IL-2, IL-6, TNF-α) were significantly reduced. Moreover, the incidence of infectious complications was lower in the intervention group. However, heterogeneity among studies was high in several analyses, warranting cautious interpretation.ConclusionNutritional support combined with conventional therapy improves nutritional and immune recovery and reduces infection risk in stroke patients. However, given the high heterogeneity and methodological limitations of included trials, the certainty of evidence remains low to very low, and these results should be interpreted cautiously.